My life : growing up native in America - Echo Hawk, Crystal (MTV Entertainment Books, 2024)
With heart, pathos, humor, and insight, twenty renowned writers, performers, athletes, and activists explore what it means to be Native American today. Through a series of essays and poems, these luminaries give voice to their individual experiences while shedding light on the depth and complexity of modern Native American identity, resiliency, and joy. From Mato Wayuhi, award-winning composer of Reservation Dogs, honoring a friend who believed in his talent to New York Times bestselling author Angeline Boulley exploring what it means to feel Native enough, these entries are not only an exploration of community, they are also a call for a more just and equitable world, and a road map toward a brighter future. Edited by IllumiNative, an organization dedicated to amplifying contemporary Native voices, My Life: Growing Up Native in America features contributions from Angeline Boulley, Philip J. Deloria, Eric Gansworth, Kimberly Guerrero, Somah Haaland, Madison Hammond, Nasugraq Rainey Hopson, Trudie Jackson, Princess Daazhraii Johnson, Lady Shug, Ahsaki Baa LaFrance-Chachere, Taietsarón:sere Leclaire, Cece Meadows, Sherri Mitchell, Charlie Amaya Scott, Kara Roselle Smith, Vera Starbard, Dash Turner, Crystal Wahpepah, and Mato Wayuhi.